Beyond the grumpy rich man and the happy peasant: Subjective perspectives on wellbeing and food security in rural India - Sarah C. White (University of Bath, Centre for Development Studies (CDS), 2013)
This paper relates different subjective approaches to wellbeing to different traditions of economic analysis. The dominant formula of 'Subjective Well-Being' is attractive because it promises a direct measure of utility, but other approaches bring different strengths to policy evaluation. 'Inner Wellbeing,' which has affinities to Sen's Capabilities Approach, is introduced. Analysis of primary data from mixed method research in rural India explores what 'happiness' and other subjective perspectives add to understanding of food security policies at a community and individual level. This shows that subjective perceptions contribute most when considered on their own terms, rather than as proxies for objective outcomes.
Keywords: 330; Subjective well-being; Inner Wellbeing; Sen's capabilities approach; food security public policy and development; India